A PET and ESIPT based fluorescent probe for the imaging of hydrogen sulfide (H2S) in live cells and zebrafish. Issue 26 (24th June 2019) - Lu, Yaru; Dong, Baoli; Song, Wenhui; Kong, Xiuqi; Mehmood, Abdul Hadi; Lin, Weiying
Abstract : H2 S is an important signaling molecule in living systems and participates in a series of physiological and pathological processes. Abstract : H2 S is an important signaling molecule in living systems and participates in a series of physiological and pathological processes. In situ and rapid detection of H2 S levels in living systems is of great importance to the in-depth study of its physiological and pathological roles. Herein, we present a new fluorescent probe (DFAN ) for the detection of H2 S in live cells and zebrafish. The probeDFAN utilized the auxiliary action of the ortho -aldehyde group to promote the thiolysis of 2, 4-dinitrophenyl ether, and achieved a highly sensitive and selective response to H2 S. The response mechanism of the probeDFAN to H2 S is an integration of PET and ESIPT mechanisms. Moreover, the probeDFAN was successfully used for the fluorescence imaging of H2 S in live cells and zebrafish.